Reference genes for gene expression profiling in mouse models of Listeria monocytogenes infection - Lethicia Souza Tavares; Roberta Lane Oliveira-Silva; Marcelo Tigre Moura; Jéssica Barboza da Silva; Ana Maria Benko-Iseppon; José Vitor Lima-Filho (BioTechniques)
RT-qPCR dissects transcription-based processes but requires reference genes (RGs) for data normalization. This study prospected RGs for mouse macrophages (pMØ) and spleen infected with Listeria monocytogenes. The pMØ were infected in vitro with L. monocytogenes or vehicle for 4 h. Mice were injected with L. monocytogenes (or vehicle) and euthanized 24 h post-injection. The RGs came from a multispecies primer set, from the literature or designed here. The RG ranking relied on GeNorm, NormFinder, BestKeeper, Delta-CT and RefFinder. B2m-H3f3a-Ppia were the most stable RGs for pMØ, albeit RG indexes fine-tuned estimations of cytokine relative expression. Actβ-Ubc-Ppia were the best RGs for spleen but modestly impacted the cytokine relative expression. Hence, mouse models of L. monocytogenes require context-specific RGs for RT-qPCR, thus reinforcing its paramount contribution to accurate gene expression profiling.